Which Truth? The Meanings of Confession in Michel Foucault (Andamios, Revista de Investigación Social, 2025)
This paper studies the different meanings with which Foucault conceived confession from the time he first approached it in Abnormal and The Will to Know, to his last texts and courses on early Christianity, with particular attention to On the Government of the Living, Wrong-doing, Truth-telling and Confessions of the Flesh. This way, the evolutions in this treatment of confession are shown, as well as its function within Christianity or the contemporary judicial system. This allows the relationship between the subject and the truth to become more complex.
Keywords: Foucault; Christianism; confession; exomologesis; exagoreusis